Effect of plant growth-promoting rhizobacteria (PGPR) on growth and yield of shallots on saline soils - Rahmandhias, Deris Trian; Karyawati, Anna Satyana; Hariyono, Didik; Maghfoer, Mochammad Dawam (Journal of Degraded and Mining Lands Management, 2024)
Soil salinity is a limiting factor in agricultural productivity. One of the biological approaches to mitigate the impact of salt stress on plants is inoculating plant growth-promoting rhizobacteria (PGPR) to the plant roots. This study aimed to investigate the eff of PGPR dosage on the growth and yield of shallots at various salinity levels. This study was carried out in the experimental field of Poncokusumo, Malang. The treatments tested consisted of two factors. The first factor was soil salinity level, consisting of four levels: no salinity, NaCl 50 mM, NaCl 100 mM, and NaCl 150 mM. The second factor was PGPR concentration, consisting of four levels: no PGPR, PGPR 10 mL/L, PGPR 20 mL/L, and PGPR 30 mL/L. The sixteen treatment combinations were arranged in a randomized block design with three replications. The data obtained were subjected to the analysis of variance (ANOVA) at a significance level limit of 5%, followed by the Honestly Significant Difference (HSD) test at a 5% significance level for any significant differences. The results showed that the application of 30 mL/L of PGPR reduced EC of the soil and improved plant height, plant dry weight, leaf area, bulb diameter, bulb weight, and the number of bulbs per plant by 33%, 47.3%, 81%, 13%, 34.2%, 98.5%, and 31%, respectively, compared to the treatment without PGPR application under NaCl 150 mM salinity. The application of PGPR at 20 and 30 mL/L dosages significantly increased chlorophyll, flavonoid, and proline indices at NaCl at 100 mM and 150 mM salinity levels compared to the treatment without PGPR.